Security Source Code Analysis of Applications in Android OS - Azam, Sami; Singh Sumra, Rajvinder; Shanmugam, Bharanidharan; Cher Yeo, Kheng; Jonokman, Mirjam; Narayana Samy, Ganthan (International Journal of Engineering and Technology, 2018)
It is a known fact that Android mobile phones’ security has room for improvement. Many malicious app developers have targeted     android mobile phones, mainly because android as an open operating system provides great flexibility to developers and there are many android phones which do not have the latest security updates. With the update of marshmallow in android, applications request           permission only during runtime, but not all users have this update. This is important because user permission is required to perform    certain actions. The permissions may be irrelevant to the features provided by an application. The purpose of this research is to          investigate the use and security risk of seeming irrelevant permissions in applications available from Google store. Two different        applications which seem to ask irrelevant permissions during installation were selected from Google store. To test these applications, static analysis, dynamic analysis and reverse engineering tools were used. Findings show potentially malicious behavior, demonstrating that downloading apps from Google play store do not guarantee security.